1988
DOI: 10.1172/jci113639
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of glutathione efflux in the perfused rat liver and isolated hepatocytes by organic anions and bilirubin. Kinetics, sidedness, and molecular forms.

Abstract: Using isolated, in situ, single-pass perfused rat livers, incubations of freshly isolated hepatocytes, and sinusoidal membrane-enriched vesicles, we and others have shown the saturability of transport (efflux) of hepatic glutathione (GSH). These observations have implicated a carrier mechanism. Our present studies were designed to provide further evidence in support of a carrier mechanism for hepatic GSH efflux by demonstrating competition by liver-specific ligands which are taken up by hepatocytes. Perfusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 19 publications
(39 reference statements)
1
14
1
Order By: Relevance
“…As shown in Fig. 2, when cultured hepatocytes were incubated with BSP-GSH (40 ,4M), total GSH efflux was inhibited by -40%, similar to that observed previously (7). Cystine (0.5 mM) coincubation did not result in further inhibition of GSH efflux.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As shown in Fig. 2, when cultured hepatocytes were incubated with BSP-GSH (40 ,4M), total GSH efflux was inhibited by -40%, similar to that observed previously (7). Cystine (0.5 mM) coincubation did not result in further inhibition of GSH efflux.…”
Section: Resultssupporting
confidence: 87%
“…Our laboratory has studied GSH transport extensively using different experimental models. The effilux ofGSH from the perfused liver and isolated hepatocytes is a saturable process (5,6) that can be competitively inhibited by organic anions, bilirubin (7), and methionine (8). Furthermore, we have shown that membrane potential is a driving force for the transport of GSH, so that hyperpolarization increases and depolarization decreases the release of GSH (9).…”
Section: Introductionmentioning
confidence: 87%
“…To the best of our knowledge, no information exists on GSH efflux from the other four cell lines. We examined basal GSH efflux and the response to DTT and BSP-GSH, which is know to cis-inhibit sinusoidal GSH transport selectively (3,6,24). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The sinusoidal GSH transporter mRNA was only expressed in liver whereas the canalicular transporter mRNA was found in all organs examined (4,5). The functional distinction between these two transporters relies on the selective cis-inhibitory effect of BSP-GSH on the sinusoidal GSH transporter but not the low affinity canalicular GSH transporter (3)(4)(5)(6). Another feature of the sinusoidal GSH transporter is its sensitivity to thiol modifying agents such that thiol reduction with dithiothreitol (DTT) led to increased GSH efflux from hepatocytes while inhibiting uptake, favoring outward movement of GSH while the opposite was observed with thiol oxidation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Sinusoidal GSH efflux is trans-inhibited by methionine and cystathionine (Aw et al, 1986;Ghibelli et al, 1998), cis-inhibited by unconjugated and mono-and diglucuronide forms of bilirubin, and sulfobromophthalein-glutathione conjugate (Aw et al, 1986;Ookhtens et al, 1988;FernandezCheca et al, 1993). Certain disulfides (cystine and oxidized glutathione disulfide) and uncharged thiols such as dithiothreitol (DTT) have opposite effects on low-affinity, high-capacity sinusoidal GSH transport (Lu et al, 1993(Lu et al, , 1994.…”
mentioning
confidence: 99%